Mixed tenure communities as a policy instrument for educational outcomes in a deprived urban context?. Issue 2 (3rd May 2016) - Robison, Oonagh; Kearns, Ade; Gray, Linsay; Bond, Lyndal; Henderson, Marion
Abstract : This article considers mixed community strategies, enacted through planning and regeneration policies, as a policy approach to the improvement of educational outcomes in schools. Analysis is undertaken of educational outcomes across secondary schools in Glasgow. The level of owner occupation in the catchment is positively associated with both examination results at S4 and positive destinations post-school, particularly at the more deprived end of the school spectrum. The results suggest that tenure mix may be both directly and indirectly related to school performance, with neighbourhood context effects not being entirely mediated through the school context.